Evaluation of real-time use of electronic patient-reported outcome data by nurses with patients in home dialysis clinics - Kara Schick-Makaroff; Anita E. Molzahn (BMC, 2017)
Abstract Background Internationally, the use of patient-reported outcomes (PROs) is increasing. Electronic PROs (ePROs) offer immediate access of such reports to healthcare providers. The objectives of this study were to assess nurses' perspectives on the usefulness and impact of ePRO administration in home dialysis clinics and assess patient perceptions of satisfaction with nursing care following use of ePROs. Methods A concurrent, longitudinal, mixed methods study was conducted over 6 months during home dialysis outpatient clinic visits in two cities. Patients (n = 99) provided ePROs using tablet computers when they visited the clinic on two consecutive occasions approximately 3 months apart. Results were scored, printed, and given to nurses before patient appointments. Patients completed satisfaction items from the Comox Valley Nursing Centre Client questionnaire following their appointments. All clinic nurses (n = 11) participated and they were each interviewed twice, three months and six months after the start of the study. Results The five themes that emerged from the interviews with the nurses include: enhancing focus of the nurses, directing interdisciplinary follow-up, offering support to patients through the process, interpreting results from the visual display, and integrating into workflow. Scores on the Client Questionnaire suggested that patients believed that they received excellent care (97%), and that the nurses perfectly understood their needs (90.9%). However, their satisfaction with care did not change over time when ePRO data was repeatedly provided to their nurses. Conclusions Nurses reported that sharing ePRO data in real-time informed their practice. Although there was no statistically significant change in patient satisfaction scores over time, some patients reported changes and benefits from the use of ePROs. Further research is needed to provide guidance about how ePRO data could enhance person-centered care.